Limitations in ROP Programs in 32 Neonatal Intensive Care Units in Five States in Mexico. (17th June 2015) - Zepeda-Romero, L. Consuelo; Gilbert, Clare
Abstract : Retinopathy of prematurity (ROP) is the main cause of avoidable blindness in children in Mexico despite National ROP Guidelines and examination of preterm infants being a legal requirement. Objective . To assess coverage of ROP programs and their compliance with national guidelines. Study Design . Thirty-two neonatal intensive care units (NICUs) in five of the largest states were visited. Staff were interviewed to collect information on their ROP programs which were defined as (1) compliant, if National Guidelines for screening and treatment were followed, (2) noncompliant, if other approaches were used, or (3) no program. Results . Only 10 (31.2%) had fully compliant programs and 11 (34.4%) had no program. In the remaining 11 (34.4%) different screening criteria were used (7 units): screening was undertaken by an ophthalmologist in unsalaried time (4), was not undertaken in the NICU (2), and was undertaken by a neonatologist (1) and/or Avastin was used as first-line treatment (7). Poorer states had poorer programs. Conclusions . Despite legislation mandating eye examination of preterm births, many ROP programs in the largest cities in Mexico require improvement or need to be established. Prevention of blindness due to ROP needs to be prioritized in Mexico to control the epidemic of ROP blindness.